The Effect of Sustainability-Based Service Quality on the Satisfaction of Beach Visitors in Jayapura City - Yensawai Engelina Rumbiak; Agustinus Numberi (Westscience Press, 2025)
The purpose of this study was to examine and determine the effect of sustainable service quality on visitor satisfaction at coastal tourist destinations in Jayapura City. The dimensions measured were tangible sustainability, sustainability practices, tangibility, reliability, responsiveness, assurance, and empathy. The study was conducted in Jayapura City. The research approach used was quantitative. Data collection used observation and questionnaire techniques (both direct and online). The respondents were visitors to coastal tourist destinations in Jayapura City. The data obtained were processed using multiple linear regression analysis tools. The results showed that the sustainability practices dimension significantly influenced visitor satisfaction at coastal tourist destinations in Jayapura City. Meanwhile, the tangible sustainability, tangibility, reliability, responsiveness, assurance, and empathy dimensions did not significantly influence visitor satisfaction at coastal tourist destinations in Jayapura City. The recommendations given to destination managers and local governments are 1) improving the quality of beach services by using environmentally friendly materials and providing trash bins as a form of waste management 2) improving the quality of services by providing standard safety equipment at beach tourism destinations 3) improving the quality of services by providing bathrooms that meet standards and good clean water quality, and 4) improving the quality of services from the aspect of human resources for beach tourism destination managers through “Sadar Wisata” socialization and other activities.